THE INFLUENCE OF INTERNAL CONTROL AND ORGANIZATIONAL COMMITMENTS ON FRAUD PREVENTION (A CASE ON KOPDIT CU PARDOMUAN PAKKAT) - Hamonangan Siallagan (Scholar Express Journals, 2022)
This study aims to examine whether Internal Control and Organizational Commitment affect the prevention of fraud either partially or simultaneously. The object of this research is the employees of CU Pardomuan Pakkat Kopdit with a total sample of 44 people. By using primary data and SPSS statistical tools, this study found evidence that internal control and organizational commitment have a positive and significant effect on fraud prevention, either partially or simultaneously. Weak internal controls that are built will provide opportunities for fraud to occur, whereas effective internal controls will prevent fraud. High commitment will create a sense of belonging, so that actions are taken fully for the betterment of the organization by avoiding fraudulent actions. Based on the results, it is suggested that in an effort to prevent fraudulent acts, it is recommended to make effective use of internal control and increase organizational commitment
Keywords: Control; Internal; Commitment; Organization